The Effect of Carbon Nanotubes on the Marshall Characteristics of AC-WC Asphalt Mixture - Akbar, Said Jalalul; Maizuar, Maizuar; Muthmainnah, Muthmainnah; Ersa, Nanda Savira; Desmi, Adzuha; Arfiandi, Joni; Adha, Ridwan; Larasati Putri, Ditya (Malikussaleh University, Aceh, Indonesia, 2025)
Carbon Nanotubes (CNTs) are cylindrical nanostructures with exceptional mechanical strength, high electrical conductivity, and excellent heat transfer capabilities, making them a promising additive in asphalt mixtures. This study investigates the effect of CNTs on the Marshall parameters of Asphalt Concrete-Wearing Course (AC-WC) mixtures using 60/70 penetration asphalt. CNTs were added to asphalt at 60°C, followed by coarse and fine aggregates preheated to 150°C. Marshall parameter tests were conducted on the samples, and the results showed a significant increase in stability compared to conventional asphalt. Asphalt stability increased by 9%, with the highest value obtained at a CNT concentration of 0.015%, reaching 2177.83 kg. The optimal stability was achieved at a CNT concentration of 0.015%. This study demonstrates that CNTs can be effectively utilized to enhance the performance of AC-WC asphalt mixtures. The flow values decreased as the CNT content increased because CNTs make the asphalt mixture stiffer, improving temperature resistance.